Bacterial community in African catfish (Clarias gariepinus) recirculating aquaculture systems under different stocking densities - Clols-Fuentes, Júlia; Nguinkal, Julien A.; Unger, Patrick; Kreikemeyer, Bernd; Palm, Harry W. (Frontiers in Marine Science, 2023)
Fish farming in Recirculating Aquaculture Systems (RAS) is a sustainable and efficient practice to produce fish. Knowledge of microbial communities, particularly harmful pathogens on fish, is required to better understand microbiological processes occurring at different RAS compartments and to optimize the overall RAS management. In this study, we assessed the influence of different Clarias gariepinus stocking densities in RAS on the water microbiome composition. Molecular targeting the V3-V4 16S rRNA hypervariable region was used to infer Amplicon Sequence Variants (ASV), identify microbes, and assess their abundance and diversity. We identified bacterial pathogens in the rearing environment associated with common fish farming practices. Our findings show that microbiomes differ across all systems (high, medium and low stocking densities) and within sampling points (water inflow, outflow and sedimentation tank). The medium-density system had the most fish biomass, resulting in high ASVs cumulative abundance. In water samples from high- and low-density systems, we discovered a wide range of phyla, with Mycobacterium sp. being the most common potentially pathogenic group. We discuss the effects of fish biomass and water physicochemical properties on the microbiome.